PENGARUH DIMENSI SUSTAINABILITY REPORTING TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA MALAYSIA - Retnosari Retnosari (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
This study aims to analyze sustainabilty dimensions of sustainability reporting positive effect on the financial performance of companies in Malaysia. This research is quantitative method of the archival research. Furthermore sampling in this study using purposive sampling and this research using descriptive analysis and multiple regression analysis.This study found existing positive influence dimensions of sustainability reporting which consists of the economic, environmental, labor, human rights, social and product responsibility on the financial performance in the company's Malaysia.Key words: corporate social responsibility, sustainability, financial performance